NASIONALISME DI PERBATASAN: REKONSTRUKSI IDENTITAS KEBANGSAAN KOMUNITAS PERBATASAN DI KABUPATEN SAMBAS KALIMANTAN BARAT - Aris - Munandar (Populis : Jurnal Sosial dan Humaniora, 2017)
This study discusses the dynamics of the interaction between state and society in the reconstruction of national identity on the community of Indonesia-Malaysia border in Sambas District, West Kalimantan, since Independence until the Reform Era. The research approach is qualitative with the ethnographic methods. The results of the study explained that the idea of nationalism and national identities are not fixed and final. In a dynamic, interpreted and constructed through negotiation, contestation, domination, and a compromise between the state and local communities, in a long period of time, and within the framework of political, economic, and socio-cultural.he rule and regulation and to conduct the law enforcement in accordance with law resemblance.